Echocardiographic analysis of acute effects of percutaneous mitral annuloplasty on severity of secondary mitral regurgitation. (2nd May 2020) - Stöbe, Stephan; Kreyer, Kristin; Jurisch, Daniel; Pfeiffer, Dietrich; Lavall, Daniel; Farese, Gerardo; Laufs, Ulrich; Hagendorff, Andreas
Abstract: Aims: Percutaneous mitral annuloplasty (PMA) represents a new treatment option for secondary mitral regurgitation (SMR) being associated with higher morbidity and mortality. The present study was aimed to evaluate whether or not acute effects on SMR severity can quantitatively be assessed after PMA. Methods and results: PMA was performed in 30 patients (mean age 76 ± 9; 37% males) with moderate ( n  = 14) or severe ( n  = 16) SMR. Vena contracta (VC), left ventricular (LV) velocity‐time‐integral ratio (VTIMV/LVOT ), effective regurgitant orifice area (EROA) by two‐dimensional proximal isovelocity surface area (PISA), regurgitant volume (RVolPISA ) and regurgitant fraction (RFPISA ) by PISA, RVolvolume and RFvolume by LV volume analyses, and parameters describing LV morphology, function, and cardiac performance were assessed by transthoracic echocardiography prior to and after PMA. According to RFPISA /RFvolume, 14 patients showed mild, 15 moderate, and 1 severe SMR after PMA. Mean RF, RVol, EROA, VC, and VTIMV/LVOT were lower directly after PMA (RFPISA : 49% ± 11 vs. 34% ± 13, P  < 0.001; RFvolume : 46% ± 10 vs. 34% ± 13, P  < 0.001; RVolPISA : 33 mL ± 13 vs. 25 mL ± 12, P  < 0.001; RVolvolume : 28 mL ± 17 vs. 20 mL ± 14, P  < 0.05; EROAPISA : 0.24 cm 2  ± 0.1 vs. 0.19 cm 2  ± 0.1, P  < 0.05; VC: 5.2 ± 0.1 vs. 4.1 ± 0.2, P  < 0.001; VTIMV/LVOT : 1.9 ± 0.4 vs. 1.6 ± 0.5, P  < 0.05). Parameters of LV morphology, function, and cardiac performance did not change directly after PMA. Conclusions: PMA leads to a reduction of MR severity in >80% of SMR patients. Acute effects of PMA can quantitatively be assessed by transthoracic echocardiography.